THE IMPORTANCE OF VACCINATION AGAINST MEASLES, RUBELLA AND MUMPS IN PREVENTING NEUROLOGICAL COMPLICATIONS IN CHILDREN - Silva Filho, Danillo Gondim da; Martins, Gabriela de Souza; Campos, Isabela Sousa; Souza, Cristiana Daniela de; Santos, Luan Bernardino Montes; Oliveira Junior, Valdivino Soares de; Soares, Erika dos Santos; Leite, Soraya de Souza Marques; Barbosa, Sarah Raquel Alves; Soares, Natascha de Prado; Borges, Daniella Afonso; Souza Júnior, Leandro Rezende de; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Childhood vaccination against measles, rubella and mumps has been a crucial measure in preventing neurological complications. These potentially debilitating and, in extreme cases, fatal diseases have significant impacts on public health. Among the most serious complications, the neurological consequences that can affect the cognitive and motor development of children stand out. With the introduction of large-scale immunization programs, there has been a substantial reduction in the incidence of these diseases, providing not only individual protection, but also contributing to the eradication of outbreaks in communities. Objective: To analyze scientific literature from the last 10 years to comprehensively understand how vaccination against measles, rubella and mumps impacts the prevention of neurological complications in children. Methodology: The review was conducted following the PRISMA checklist guidelines. We used the PubMed, Scielo and Web of Science databases to search for relevant articles. The descriptors were "vaccination", "measles", "rubella", "mumps" and "neurological complications". Inclusion criteria covered studies published in the last 10 years, focused on children and addressing post-vaccination neurological effects. Exclusion criteria included studies with unrepresentative samples and lack of detailed information on neurological outcomes. Results: The analysis revealed a significant reduction in neurological complications associated with measles, rubella and mumps after the implementation of vaccination programs. Studies have highlighted the effectiveness of vaccines in preventing encephalitis and other neurological sequelae. Additionally, a decline in hospitalizations related to these complications was observed. Conclusion: This systematic review reinforces the importance of vaccination in preventing neurological complications in children resulting from measles, rubella and mumps. Analysis of the last 10 years reinforces the effectiveness of vaccines, highlighting not only the individual benefits, but also the public health gains in preventing outbreaks and reducing the serious consequences associated with these diseases.